River's end - Roberts, Nora.; Copyright Paperback Collection (Library of Congress) (New York : Jove Books, 2000)
Traumatized by the events surrounding the breakup of her parent's marriage years ago, a young woman seeks to confront her past and know the truth about the infamous night in her life that has become a part of Hollywood history.
Pages [447]-461: Preview chapter one of the author's Tears of the moon, the second book of a trilogy, c2000.
Keywords: Motion picture actors and actresses; Children of celebrities